Slow Degradation and Aggregation In Vitro of Mutant GABA(A) Receptor γ2(Q351X) Subunits Associated with Epilepsy - Kang, Jing-Qiong (Society for Neuroscience, 2010)
The GABA(A) receptor γ2 subunit nonsense mutation Q351X has been associated with the genetic epilepsy syndrome generalized epilepsy with febrile seizures plus, which includes a spectrum of seizures types from febrile seizures to Dravet syndrome. Although most genetic epilepsy syndromes are mild and remit with age, Dravet syndrome has a more severe clinical course with refractory seizures associated with developmental delay and cognitive impairment. The basis for the broad spectrum of seizure phenotypes is uncertain. We demonstrated previously that the GABA(A) receptor γ2 subunit gene Q351X mutation suppressed biogenesis of wild-type partnering α1 and β2 subunits in addition to its loss of function. Here we show that γ2S(Q351X) subunits have an additional impairment of biogenesis. Mutant γ2(Q351X) subunits were degraded more slowly than wild-type γ2 subunits and formed SDS-resistant, high-molecular-mass complexes or aggregates in multiple cell types, including neurons. The half-life of γ2S(Q351X) subunits was ∼4 h, whereas that of γ2S subunits was ∼2 h. Mutant subunits formed complexes rapidly after synthesis onset. Using multiple truncated subunits, we demonstrated that aggregate formation was a general phenomenon for truncated γ2S subunits and that their Cys-loop cysteines were involved in aggregate formation. Protein aggregation is a hallmark of neurodegenerative diseases, but the effects of the mutant γ2S(Q351X) subunit aggregates on neuronal function and survival are unclear. Additional validation of the mutant subunit aggregation in vivo and determination of the involved signaling pathways will help reveal the pathological effects of these mutant subunit aggregates in the pathogenesis of genetic epilepsy syndromes.